ANALYSIS OF THE TANJORE MARATHAS' PAINTINGS - S. VIMALA (RADJA PUBLIKA, 2022)
Tanjore, Tamil Nadu's rice bowl, is also home to the arts. The kings' paintings are excellent examples of their Maratha painting abilities. During their rule in the Tanjore Maratha era. These are pieces of art that will not deteriorate with the passage of time. Tanjore style of painting is a style that flourished in Tamil Nadu from 16th to 18th century. It was influenced by the Andhra style of the Nayaks, Maratha and Mughal style and English Manatee style. Tanjore paintings adorned the interiors of the palaces. These style paintings were created by them as a clan profession. The Tanjore Brihadisvara Temple is the only temple in the world with a thousand-year-old artwork as well as a range of subsequent works. The art that grew up in this temple eventually gave birth to a new painting style known as Tanjore style painting. That is the current depiction of Tanjore artwork.